Entrepreneurship in international marketing - Zou, Shaoming; Xu, Hui; Shi, Linda Hui (Emerald, 2015)
The latest volume in the Advances in international marketing series is a fresh addition to the international marketing literature, expanding the current knowledge in several significant ways. Divided in to two sections, the first part of Vol. 25 addresses important issues concerning entrepreneurship in the international market. Pulling together papers authored by well-known scholars they look at issues such as born-global firms evolution, market orientation, alliance capabilities, customer orientation, and performance in the global market. Collectively, these papers shed significant new light on the role of entrepreneurship in born-global firms and exporting firms. The second part of Entrepreneurship in International Marketing brings together a collection of papers dealing with contemporary international marketing issues, including the conceptual domain of international marketing, global brands and luxury brands in emerging markets, international retail supply chains, and exit behaviour of FDI firms.
Keywords: Export marketing.; Entrepreneurship.; elektronické knihy; electronic books